Identification of Wheat Germplasm Resistance to Late Sowing - Samia Mahgoub Omer Basheir; Yi Hong; Chao Lv; Hongwei Xu; Juan Zhu; Baojian Guo; Feifei Wang; Rugen Xu (Agronomy, 2023)
To evaluate the performance of wheat plant height and spike-related traits under delayed sowing conditions, a screening trial was conducted for wheat germplasm that exhibits resistance to late sowing and early maturity. The differences and stability of plant height and spike-related traits under different sowing dates were analyzed using 327 wheat germplasm sources from a wide range of areas. The results showed that mean values of wheat plant height and spike-related traits generally decreased along with the delay in sowing dates. Broad-sense heritability of plant height (PH), internode length below spike (ILBS), spike length (SL), spikelet per spike (SPS), and spike number (SN) under multiple environments were all above 85%. Ten varieties, including Xiangmai 35, Pingyang 27, Huaimai 23, Huaimai 22, Emai 6, Zhenmai 12, Xiaoyan 81, Shannong 7859, Annong 1589, and Shuiyuan 86 indicated stable performance under different sowing dates, which harboring good resistance to late sowing. The results of this study laid a foundation for breeding high-yield wheat varieties that are resistant to late sowing.